Holistic Management in Pulmonary Tuberculosis Patients with Malnutrition - Karyus, Aila (Faculty of Medicine, Public Health, and Nursing, 2023)
Background: Tuberculosis (TB) is still a problem in developing countries and even the world. TB is one of the top 10 causes of death and the first cause of death from an infectious agent worldwide. The government plans to eliminate TB by 2030, which is carried out with the National Strategy for TB Control. Family doctors play an important role in which the role of family doctors is not only to cure but also to promote health and prevention of TB disease. Purpose: The application of evidence-based medical doctor family services to patients by identifying risk factors, clinical problems, and management with a patient-centered approach and family approach. Method: The study conducted was a Case Report. Primary data were obtained through history taking and physical examination by making home visits, filling family folders, and filling patient files. The assessment was carried out based on the initial holistic diagnosis, process, and end of the visit quantitatively and qualitatively. Results: Based on a holistic diagnosis, it was found that an 87-year-old patient complained of coughing, difficulty in swallowing, and weight loss since three months ago, three weeks ago the patient was diagnosed with TB. Physical examination showed a BMI of 14.2. The patient had difficulty swallowing, with the examination of nerves 10 within normal limits. Internal risk factors include a lack of knowledge about TB, and aging. External factors are often exposed to dust. Functional degrees 4. Four visits were made. The interventions provided in the form of education about TB include the definition, symptoms, treatment and prevention, counseling with the family, and providing a high-calorie, high-protein diet for patients. The evaluation results show an increase in patient and family knowledge about TB and an improvement in the patient's diet that the family has done. Conclusion: The diagnosis of TB with malnutrition and dysphagia is good. Management provided is in accordance with the guidelines, visible changes in behavior, and knowledge of patients and patients' families after an intervention based on evidence-based medicine that is patient-centered, family approach.